A colorimetric fluorescent probe for rapid and specific detection of nitrite. (1st December 2019) - Xu, Zujun; Shi, Wenxiu; Yang, Chengjun; Xu, Jing; Liu, Huapeng; Xu, Jing; Zhu, Baocun
Abstract: The method of fluorescent probes has been an important technique for detection of nitrite (NO2 − ). As an important inorganic salt, excessive nitrite would threaten humans and the environment. In this paper, a colorimetric fluorescent probe P‐N (1, 2‐diaminoanthraquinone) with rapid response and high selectivity, which could detect NO2 − by visual colour changes and fluorescence spectroscopy is presented. The probe P‐N solution (pH 1) changed from pink to colourless with the addition of NO2 − and fluorescence intensity at 639 nm clearly decreased. Good linear exists between fluorescence intensities and NO2 − concentrations for the range 0–16 μM, and the detection limit was 54 nM (based on a 3σ/slope). Moreover, probe P‐N could also detect NO2 − in real water samples, and results were all satisfactory. Probe P‐N shows great practical application value for detecting NO2 − in the environment.